Modified dealer model for the electricity market - Gong, Xue (2015)
After a worldwide reformation of electricity market since 1990s, the electricity market has been transformed from regulated and monopolistic to partially deregulated. The most striking feature of electricity price in deregulated market is spiking which is the subject of this paper. No commonly accepted model exist can describe this phenomenon in a satisfactory way. This problem is interesting to physics because nancial problems can be successfully studied using methods and models from physics and physics bene ts from this interdisciplinary study. The dealer model is an agent-based model proposed in 1992 by Prof Hideaki Takayasu to study stock market. In this paper, an modi ed dealer's model will be implemented to study the deregulated electricity market. The model will be compared with real world data from Italian Electricity Exchange. A spike statistics analysis will be performed to show that the model replicate the major statistical feature of the real world data. Further analysis on the characteristics emerging from the model will be presented.